New insights in RBM20 cardiomyopathy - Lennermann, David; Backs, Johannes; Hoogenhof, Maarten van den (Current heart failure reports)
This review aims to give an update on recent findings related to the cardiac splicing factor RNA-binding motif protein 20 (RBM20) and RBM20 cardiomyopathy, a form of dilated cardiomyopathy caused by mutations in RBM20.